FARMER EMPOWERMENT AND ITS CONTRIBUTING FACTORS (A CASE STUDY OF PATCHOULI FARMER IN KABUPATEN ACEH JAYA) - Zikri, Irfan; Agussabti, Agussabti; Akram, Muhammad; Indra, Indra; Kamaruzzaman, Suraiya; Mujiburrahmad, Mujiburrahmad; Susanti, Elly (Jurnal AGRISEP, 2022)
Kabupaten Aceh Jaya is a very potential Aceh patchouli production center. The development of the patchouli industry sector in Aceh faces serious challenges, especially the capacity building of farmers towards good agriculture practices, and innovation and technology. This study aims to identify the level of empowerment of farmers and the affecting factors. The study employed a questionnaire survey to 88 samples from 383 populations. Data analysis used a descriptive method and chi-square test. The results show that a low level of farmer empowerment is predominantly. The weakest elements are the ability to cooperate and solidarity; meanwhile, the ability to overcome obstacles is the highest, followed by the awareness and desire to change, and the ability to increase capacity to gain access. Farmer's perceptions on the group institutions, and program intervention have a significant association with empowerment, while the perception to characteristics of the social systems has no relationship. Therefore, the role of empowerment innovation is necessary for capacity building.